The Challenges of Productivity Growth in the Small Island States of Europe: A Critical Look at Malta and Cyprus - Silvio J. Camilleri; Joseph Falzon (Island Studies Journal, 2013)
This paper looks at productivity growth rates in Malta and Cyprus and proposes policies as to how these island states might augment their productivity and competitiveness. We identify three possible growth strategies for the two islands: an Innovation-Oriented Economy, a Controlled Input-Cost Economy and an Opportunistic Growth Model. In order to infer which strategy might be best suited to the two states, we conduct a comparative analysis amongst different EU countries in terms of productivity yardsticks. We also evaluate trends in gross value added (GVA), employment levels, and unit labour costs (ULCs) in the most important economic sectors of Malta and Cyprus. The research suggests that a Controlled-Input Cost model is best suited to most Maltese and Cypriot economic sectors. Possible policies aimed at fostering future growth and competitiveness in the island states are proposed